Proceeding of Colloquium on Robotics, Unmanned Systems and Cybernetics 2014 - Addie Irawan, Hashim; et, al. (Penerbit Universiti Malaysia Pahang, 2015)
Colloquium on Robotics, Unmanned Systems and Cybernetics 2014 (CRUSC 2014) is one of the initiatives from Robotics and Unmanned System (RUS) research group under the Instrumentation and Control Engineering (iCE) Cluster, Faculty of Electrical & Electronics Engineering, Universiti Malaysia Pahang (UMP) to bring together the researchers that related to the field of robotics, unmanned systems and cybernetics. In this first CRUS event the targeted is to bring majority participants among the undergraduates and postgraduate under related research/focus group to submit research papers, concept papers, technical report or undergraduate final year project report.